Large A.C. Machines Theory and Investigation Methods of Currents and Losses in Stator and Rotor Meshes Including Operation with Nonlinear Loads - Boguslawsky, Iliya; Korovkin, Nikolay; Hayakawa, Masashi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2017)
In this monograph the authors solve the modern scientific problems connected with A.C. motors and generators, based first on the detailed consideration of their physical phenomena. The authors describe the theory and investigative methods they developed and applied in practice, which are considered to be of essential interest for specialists in the field of the electrical engineering industry in European countries, the USA, Argentina, and Brazil, as well as in such countries as India, China, and Iran. This book will be of interest to engineers specialized in the field of the manufacture, operation, and repair of A.C. machines (motors and generators) as well as electric drives; to professors, lecturers, and post-graduate students of technical universities, who are specializing in the field of electric machine engineering and electric drives; and to students who are engaged in the field of high current techniques, electric drives, and electric machine engineering.
Problems formulation -- Investigation methods of performance characteristics for double-fed machines with converter in rotor circuit. Summary of main investigation stages of A.C. machines -- Stator MMF harmonics at non-sinusoidal machine power supply (for m≥1, O≥1) -- Peculiarities of currents investigation in magnetically coupled circuits for A.C. machines with short-circuited rotor windings -- Representation of currents in rotor short-circuited winding elements in the form of generalized characteristics -- Passive quadripoles; recurrent circuits of various structure. Investigation of their peculiarities for modeling process of currents distribution in short-circuited rotor windings -- Active symmetrical and asymmetrical chain circuits. Investigation of their peculiarities for modeling process of currents distribution in short-circuited rotor windings -- EMF induced by resulting field in short-circuited loops of damper winding and squirrel cage -- Investigation methods of currents distribution in regular damper windings and squirrel cages -- Investigation methods of currents distribution in squirrel cages with asymmetry -- Investigation methods of currents distribution in irregular damper windings -- MMF of damper winding, squirrel cage (at asymmetry in them or at its absence) and excitation winding. Representation of MMF in the form of harmonic series in complex plane -- Field harmonics in air gap of A.C. machine in nonlinear network -- System of equations for magnetically coupled loops for A.C. machine in nonlinear network -- Peculiarities of operation modes of alternating current machine with short-circuited rotor windings at nonsinusoidal power supply -- Operation problems of high-power A.C. machines in nonlinear network -- Frequency-controlled induction motors in nonlinear networks: assessment criteria of higher harmonics influence. Method of criteria calculation -- Method of minimizing losses in high-power low-speed frequency-controlled motors in operation modes at nonlineardependence of shaft torque on rotation speed -- Methods of decreasing nonlinear distortion factor in voltage curve of salient-pole generator. Investigation of EMF tooth harmonics of its multiphase winding with q per pole and phase as integer -- Methods of decreasing nonlinear distortion factor in voltage curve of double-fed machines. Investigation of EMF tooth harmonics of its multiphase stator and rotor windings with q per pole and phase as integer -- Method of determination stator winding MMF at arbitrary phase current waveform and unequal width of phase zones (for investigation of operational characteristics of frequency - controlled motors) -- Investigation method of transient modes in induction machines with rotor cage asymmetry -- Theory and methods of investigation of eddy currents and additional losses in stator windings.
Keywords: Electric power production; Control engineering; Electrical Power Engineering; Mechanical Power Engineering; Control and Systems Theory